A Deca‐9‐Fluorenolato‐deca‐Samarium Oxide Cage. Issue 20 (18th May 2018) - Werner, Daniel; Deacon, Glen B.; Junk, Peter C.
Abstract : The 9‐fluorenone (fn) ketyl in [Yb III (DippForm)2 (fn · ‐O)] {DippForm = N, N′ ‐bis(2, 6‐diisopropylphenyl)formamidinate}, underwent reduction to the dianion (C13 H8 ‐O) upon single electron transfer from Sm II I2 (thf)2 . The dianion was obtained as a decanuclear, deca‐9‐fluorenolato, tetraoxido mixed‐oxidation‐state samarium cage [Sm10 O4 {(C13 H8 )‐O}10 (thf)10 ], obtained after ligand redistribution. The structure is relevant to the deoxygenation of ketones by lanthanoid metals. Abstract : The 9‐fluorenone (fn) ketyl in [Yb III (DippForm)2 (fn′ ‐O)] {DippForm = N, N′ ‐bis(2, 6‐diisopropylphenyl)formamidinate}, undergoes reduction to the dianion upon single electron transfer from Sm II I2 (thf)2 . The dianion was obtained as a decanuclear, deca‐9‐fluorenolato, tetraoxido mixed‐oxidation‐state samarium cage, and the chemistry is relevant to the deoxygenation of ketones by lanthanoid metals.